Synergistic Antioxidant and Anti-Inflammatory Activities of Kale Juice Fermented with Limosilactobacills reuteri EFEL6901 or Limosilactobacills fermentum EFEL6800 - Ga Yun Kim; Seul-Ah Kim; Sun Young Kong; Hyunbin Seong; Jae-Han Bae; Nam Soo Han (MDPI AG, 2023)
This study investigates the synergistic impact of fermenting kale juice with Limosilactobacillus strains on its antioxidant and anti-inflammatory properties. Kale's rich nutrient profile, especially its flavonoids, offers potential health benefits. Probiotic lactic acid bacteria are employed in kale fermentation to enhance nutrient bioavailability and generate bioactive compounds. Kale juices fermented with L. reuteri EFEL6901 or L. fermentum EFEL6800 exhibited superior microbial growth. Free sugars and amino acids were converted to alcohols and organic acids, affecting the organoleptic and health-related properties of the product. In addition, fermentation increased quercetin and kaempferol content, indicating improved availability. Furthermore, the fermented juice exhibited notable antioxidant activity and suppressed nitric oxide (NO) production, revealing anti-inflammatory potential. Gene expression analysis confirmed reduced pro-inflammatory markers such as iNOS, COX-2, IL-6, and IL-1β and elevated anti-inflammatory cytokines, including IL-10. This research highlights the promising potential of fermented kale juice, enriched with Limosilactobacillus strains, as a functional food with combined antioxidant and anti-inflammatory benefits.